2014
DOI: 10.1021/jz501264x
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Perspective of Ultrafast Charge Transfer at a Dye–Semiconductor Interface

Abstract: Understanding interfacial charge-transfer processes on the atomic level is crucial to support the rational design of energy-challenge relevant systems such as solar cells, batteries, and photocatalysts. A femtosecond time-resolved core-level photoelectron spectroscopy study is performed that probes the electronic structure of the interface between ruthenium-based N3 dye molecules and ZnO nanocrystals within the first picosecond after photoexcitation and from the unique perspective of the Ru reporter atom at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 49 publications
(132 reference statements)
7
83
0
2
Order By: Relevance
“…The general similarities between the transients of germanium and silicon-germanium [Fig. 3(b)] strongly corroborate that the reporter atom concept 20 is successfully applied here to solids and that germanium atoms can be employed to probe the carrier dynamics of electrons and holes in the Si-like indirect gap alloy. Other recent findings by Santomauro et al 40 suggest that this is expected to be true for carriers that are either localized near the germanium atoms or delocalized in the alloy.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The general similarities between the transients of germanium and silicon-germanium [Fig. 3(b)] strongly corroborate that the reporter atom concept 20 is successfully applied here to solids and that germanium atoms can be employed to probe the carrier dynamics of electrons and holes in the Si-like indirect gap alloy. Other recent findings by Santomauro et al 40 suggest that this is expected to be true for carriers that are either localized near the germanium atoms or delocalized in the alloy.…”
Section: Resultssupporting
confidence: 56%
“…The samples are nanocrystalline with domain sizes of ∼2.5 nm, grown by low-pressure chemical vapor deposition (LPCVD). Herein, the germanium atoms are employed as reporter atoms 20 for probing the carrier dynamics in the alloy with sensitivity to electrons and holes. The transient absorption (TA) data is captured at the M 4,5 -edge of the germanium atoms in the silicon-germanium alloy and, by decomposing the TA data into contributions of electronic state blocking of optically excited carriers and band shifts, the carrier dynamics are retrieved (see also supplementary material, Sec.…”
Section: Introductionmentioning
confidence: 99%
“…However, pioneering PES experiments on solids at FELs have revealed several experimental challenges 14–16 . A very recent time resolved PES study of charge transfer on a molecular dye absorbed on a surface has shown the possibility of performing dynamical chemical analysis at FELs; 17 however, the application to other systems requires a detailed study due to the difficulties in the data interpretation because of modifications in the PES spectra known as vacuum space charge effects 18 . In particular, the electrons photoemitted from the sample within the duration of a femtosecond X-ray pulse can be described as enclosed in a cloud of charges originated from the sample and travelling to the analyser 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results point in the same direction as recently published measurements that showed the formation of a transient electronic configuration that gives rise to a distribution of transition states. 12 They have two implications for applications: first, the transient configuration can present a bottle-neck for HET as discussed by Siefermann et al 12 Second, it gives the opportunity to independently design a favorable chromophore and adjust the level alignment by introducing dipole groups that shift the donor level just above the conduction band edge and thus optimizes open circuit voltage for the respective chromophore without altering charge separation efficiency. A similar result has been presented recently.…”
Section: Introductionmentioning
confidence: 99%